1969
DOI: 10.1111/j.1095-8339.1969.tb01966.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of the tuber in seedlings of five species of Dioscorea from Nigeria

Abstract: Tubers in all five species develop from the hypocotyl region of the seedlingS. A perivascular cambium arises cutting off mainly starch‐storing parenchyma and collateral vascular bundles to the inside. A phellogen gives rise to cork on the outside. Between the two cambial layers there may or may not be layers of parenchyma, not storing starch but containing raphides. The vascular bundles consist of xylem with vessels, scalariform tracheids and parenchyma; and phloem, with sieve tubes and parenchyma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…However, it has not been reported that independent tissue like root caps is formed at the tips of the tubers in Dioscorea. In fi ve species of Dioscorea, the fi rst indication of tuberization was the formation of perivascular cambium in the hypocotyl region, and the shape of the tuber depended on the local persistence of meristematic zone (Lawton and Lawton, 1969). In Dioscorea cayenensisDioscorea rotundata complex, the subapical meristematic zone is formed at the apex of tuber (Trouslot et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has not been reported that independent tissue like root caps is formed at the tips of the tubers in Dioscorea. In fi ve species of Dioscorea, the fi rst indication of tuberization was the formation of perivascular cambium in the hypocotyl region, and the shape of the tuber depended on the local persistence of meristematic zone (Lawton and Lawton, 1969). In Dioscorea cayenensisDioscorea rotundata complex, the subapical meristematic zone is formed at the apex of tuber (Trouslot et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…is a kind of yams and the tuber growing underground is used mainly as food. Organographically, the tuber of Dioscorea is generally regarded as a stem tuber (Burkill, 1960;Lawton and Lawton, 1969) but has some characteristics different from the potato (Solanum tuberosum) and other conventional stem tubers. In yam tubers, the surface is devoid of scale leaves and identifi able nodes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 -12 In view of the influence of sprouting on postharvest losses, efforts have been made to prolong dormancy by applying sprout regulators (reviewed by Barker et al 9 ). The most promising, affordable and reliable active compound is gibberellic acid (GA 3 ). 15,16 The established method of application is that used by Martin,14 in which tubers are de-cormed and soaked for varying lengths of time in a solution of 150 to 500 mg kg −1 of GA 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The most promising, affordable and reliable active compound is gibberellic acid (GA 3 ). 15,16 The established method of application is that used by Martin,14 in which tubers are de-cormed and soaked for varying lengths of time in a solution of 150 to 500 mg kg −1 of GA 3 . The immersion period was reduced drastically from 22 h to between 2 and 6 h. 17 -19 Instead of treating the whole tuber, dipping the apex proved to be sufficient.…”
Section: Introductionmentioning
confidence: 99%